2020
DOI: 10.1002/anie.202001989
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Shelled C@MoS2 Structures Preloaded with Sulfur: An Additive Reservoir for Stable Lithium Metal Anodes

Abstract: The growth of Li dendrites hinders the practical application of lithium metal anodes (LMAs). In this work, a hollow nanostructure, based on hierarchical MoS2 coated hollow carbon particles preloaded with sulfur (C@MoS2/S), was designed to modify the LMA. The C@MoS2 hollow nanostructures serve as a good scaffold for repeated Li plating/stripping. More importantly, the encapsulated sulfur could gradually release lithium polysulfides during the Li plating/stripping, acting as an effective additive to promote the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 51 publications
0
54
0
Order By: Relevance
“…Unfortunately, the practical application of Li metal anodes (LMAs) has not been realized due to the structural and interfacial instability issues induced by the uncontrollable growth of Li dendrites during repeated electrochemical cycling processes [9–11] . Extensive efforts have been recently made to regulate the Li deposition/dissolution properties for stable LMAs, including developing compatible electrolytes, [12–16] engineering rationally designed three‐dimensional (3D) scaffolds for Li accommodation, [17–20] and constructing artificial solid–electrolyte interphase (SEI) layers [21–24] . Among these approaches, 3D host nanostructures for LMAs have shown outstanding electrochemical properties because of the largely decreased local current density and accommodated huge volume variation during Li accommodation/extraction [25, 26] .…”
Section: Figurementioning
confidence: 99%
“…Unfortunately, the practical application of Li metal anodes (LMAs) has not been realized due to the structural and interfacial instability issues induced by the uncontrollable growth of Li dendrites during repeated electrochemical cycling processes [9–11] . Extensive efforts have been recently made to regulate the Li deposition/dissolution properties for stable LMAs, including developing compatible electrolytes, [12–16] engineering rationally designed three‐dimensional (3D) scaffolds for Li accommodation, [17–20] and constructing artificial solid–electrolyte interphase (SEI) layers [21–24] . Among these approaches, 3D host nanostructures for LMAs have shown outstanding electrochemical properties because of the largely decreased local current density and accommodated huge volume variation during Li accommodation/extraction [25, 26] .…”
Section: Figurementioning
confidence: 99%
“…Furthermore, they also designed a hollow nanostructure based on hierarchical MoS 2 hollow carbon particles preloaded with sulfur (C@MoS 2 /S) for Li storage (Figure 8d). [ 106 ] The observation of cryo‐TEM showed that the hollow C@MoS 2 could be used as a good scaffold for repeated deposition of Li metal. In the initial nucleation stage, Li ions will intercalate into the MoS 2 nanosheets, which may benefit to weaken the interfacial resistance and enable fast Li diffusion.…”
Section: The Identification Of Seimentioning
confidence: 99%
“…However, the uncontrollable growth of Li dendrites and collapse of the solid electrolyte interphase (SEI) layer lead to low Coulombic efficiency (CE) and deteriorated cycling performance, which largely restrict the practical application of the Li metal anode (LMA) (7)(8)(9)(10)(11)(12)(13). Considerable efforts have been made to regulate the Li plating/ stripping behaviors for stable Li metal batteries, including developing functional electrolytes (14)(15)(16)(17)(18), constructing well-designed three-dimensional (3D) host structures (19)(20)(21)(22)(23)(24), and using artificial protection layers (25)(26)(27)(28)(29)(30). Despite much progress (31,32), it remains a challenge to explore LMA with stable cycling life over 500 cycles at practical current densities greater than 1 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%